Adsorption of dibenzothiophene in model diesel fuel by amarula waste biomass as a low-cost adsorbent. (1st May 2022) - Kabi, Tsepiso; Hildebrandt, Diane; Liu, Xinying; Yao, Yali
Abstract: The effectiveness of the adsorption process is determined by the type of adsorbent used, but some adsorbents require a significant amount of processing to achieve the desired quality, and this has become a drawback economically and environmentally. This study focused on mitigating the issue of waste management and land pollution by using amarula waste biomass, which is a low-cost adsorbent that is obtained from the industrial waste by-product. The amarula shell (AmSh) waste was found to have a higher adsorption efficiency of 30 ± 3% compared to the amarula seed (AmSe) waste and the amarula fruit (AmWa) waste, which had 19 ± 5% and 9.5 ± 0.7% efficiency, respectively. It was found that the amarula waste biomass performed better at lower adsorption temperatures. The adsorption capacity was found to decrease with an increase in the quantity of the biomass. Kinetic models were applied to the experimental data. Thermodynamic parameters were also studied to determine the spontaneity of the adsorption process. The characteristics of both the fresh and used amarula waste biomass was analyzed by using Fourier Transform Infrared Spectroscopy (FTIR), Field Emission Scanning Electron Microscopy with Energy Dispersive Spectroscopy (FESEM-EDS), Brunauer-Emmett-Teller (BET) and Thermogravimetric Analysis (TGA). It was then concluded that cellulose and hemicellulose structures in amarula waste biomass played a major role in reducing the content of dibenzothiophene in model diesel fuel. Highlights: The Amarula wastes biomass reduced the content of toxic Dibenzothiophene in Fuels. Crystallography and heteroatoms in biomass structure affect adsorption efficiency. Kinetics, Isotherms, thermodynamics parameters evaluated the adsorption mechanism. A sustainable low-cost green adsorbent mitigates both land and air pollution.